Scatterlings eaudiobook A novel. - Manenzhe, Resoketswe Martha (HarperAudio, 2022)
A BEST NEW BOOK from *Vanity Fair *The Root *Vulture *People *The Washington Post *Christian Science Monitor *Los Angeles Times *Essence A New York Times Book Review Editor's Choice Pick! A New Yorker Best Book of the Year! A lyrical, moving novel in the spirit of Transcendent Kingdom and A Burning—and the most awarded debut title in South Africa—that tells the story of a multiracial family when the Immorality Act is passed, revealing the story of one family's scattered souls in the wake of history. In 1927, South Africa passes the Immorality Act, prohibiting sexual intercourse between "Europeans" (white people) and "natives" (Black people). Those who break the draconian new law face imprisonment—for men of up to five years; for women, four years. Abram and his wife Alisa have their share of marital problems, but they also have a comfortable life in South Africa with their two young girls. But then the Act is passed. Alisa is black, and their two children are now evidence of their involvement in a union that has been criminalized by the state. At first, Alisa and Abram question how they'll be affected by the Act, but then officials start asking questions at the girls' school, and their estate is catalogued for potential disbursement. Abram is at a loss as to how to protect his young family from the grinding machinery of the law, whose worst discriminations have until now been kept at bay by the family's economic privilege. And with this, his hesitation, the couple's bond is tattered. Alisa, who is Jamaican and the descendant of slaves, was adopted by a wealthy white British couple, who raised her as their child. But as she grew older and realized that the prejudices of British society made no allowance for her, she journeyed to South Africa where she met Abram. In the aftermath of the Immorality Act, she comes to a heartbreaking conclusion based on her past and collective history – and she commits her own devastating act, one that will reverberate through their entire family's lives. Intertwining her storytelling with ritual, myth, and the heart-wrenching question of who stays and who leaves, Scatterlings marks the debut of a gifted storyteller who has become a sensation in her native South Africa—and promises to take the Western literary world by storm as well.